Lessons from the great recession at the crossroads of sustainability and recovery - Gurdgiev, Constantin T.; Leonard, Liam; Gonzalez-Perez, Maria-Alejandra (Emerald, 2016)
This volume examines global cases of environmental sustainability and economics in the context of nations from multi-disciplinary perspectives. This book analyses the problems faced globally as economies try to build a sustainable future in the aftermath of the 'Great Recession', and the recent economic and financial crises.
Keywords: Business & Economics -- Development -- Sustainable Development.; Environmental economics.; Economic stabilization.; Sustainable development.; Global Financial Crisis, 2008-2009.; elektronické knihy; electronic books